Quantitative Trait Loci Analysis of White Mold Avoidance in Pinto Bean. Issue 5 (1st September 2015) - Hoyos‐Villegas, Valerio; Mkwaila, Wezi; Cregan, Perry B.; Kelly, James D.
ABSTRACT: White mold is a major disease of common bean ( Phaseolus vulgaris L.) grown in temperate production areas. The objective of this study was to use single nucleotide polymorphism (SNP) markers from the BARCBean6K_3 BeadChip to identify quantitative trait loci (QTL) associated with traits related to white mold resistance in common bean. A recombinant inbred line (RIL) population from a cross of disease‐tolerant pinto line AN‐37 and disease‐susceptible line P02630 was evaluated in Michigan for 4 yr under white mold pressure. Traits evaluated included disease incidence, the numbers of days to flower and to maturity, canopy height, lodging, seed yield, and 100‐seed weight. A linkage map of the RIL population spanning 1499 cM was constructed using 447 SNP markers. The map covered all 11 bean chromosomes with an average distance of 3.6 cM between markers. A total of 13 QTL for agronomic and disease traits were consistently identified in different years. A major QTL WM3.1 AN associated with white mold avoidance was validated on chromosome Pv03. The QTL is associated with disease avoidance traits such as canopy porosity, plant height, stay green stem trait, and maturity. Quantitative trait loci for maturity and canopy height also mapped to the same genomic region on Pv03. Finding strong associations between maturity, lodging, canopy height, and disease incidence offers alternative strategies to improve levels of white mold avoidance over greenhouse screening. The validation of the WM3.1 AN, AP630 QTL for white mold avoidance should provide bean breeders with the opportunity to introgress avoidance traits into their germplasm.